The Religious Authority of Anre Gurutta’ K.H. Muhammad As`Ad in the Spread of Cultural Da'wah in South Sulawesi - Nurhikmah Nurhikmah; Muhammad Taufiq Syam (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2026)
Cultural da'wah has become an integral part of the history of da'wah development in Indonesia, including Anre Gurutta’ K.H. Muhammad As'ad, founder of the As'sadiyah Islamic Boarding School in Wajo, South Sulawesi. This study aims to analyze the patterns of religious authority of Anre Gurutta’ K.H. Muhammad As'ad and his role in cultural da'wah strategies that contributed to the spread of Islam in South Sulawesi. A descriptive qualitative research method with a phenomenological approach was used to analyze and narratively present all aspects related to the relevance of religious authority in the implementation of cultural da'wah in traditional Islamic boarding schools in South Sulawesi, based on observations and interviews with the relevant sources. The results of this study indicate that the religious authority of Anre Gurutta’ K.H. Muhammad As'ad was shaped by traditional, rational-legal, and charismatic authority, which contributed to the spread of pesantren-based cultural da'wah in South Sulawesi. The role of religious authority figures is expected to strengthen religious moderation through cultural da'wah in Indonesia.